Different Reaction Patterns of Caregivers of Children With Imperforate Anus: A Latent Profile Analysis - Wang, Dan; Xu, Hongzhen; Liu, Kexian; Tou, Jinfa; Jia, Yushuang; Gao, Wei; Chen, Xiaofei; Luo, Feixiang (Frontiers in Pediatrics, 2022)
Aim: This study aimed to explore how different dimensions of caregivers’ reaction shape their caring experience, and the factors associated with different reaction patterns. Design: A second analysis of a multisite cross-sectional study were conducted. Caregivers of children with IA were enrolled in three tertiary children’s hospitals in Eastern China between November 2018 and February 2019. Methods: The caregivers’ experience, stigma feeling, social support level and perception of uncertainty were assessed by Caregiver Reaction Assessment, Parent Stigma Scale, Social Support Scale and Parents’ Perception of Uncertainty Scale accordingly. The demographic information of caregivers as well as the children’s clinical data were collected. Latent profile analysis was conducted to determine different patterns of caregivers’ reaction, and logistics analysis was used to explore the associated factors of the reaction pattern. Findings: A total number of 229 caregivers (median age = 30, quartiles: 28, 36 ) were included. Three distinguishable caregiving reaction types were identified (Class 1: low burden and high benefit, 4.8%; Class 2: moderate burden and benefit, 48.9%; Class 3: high burden and low benefit, 46.3%). In logistics analysis, the Class 1 and Class 2 were combined as one group due to the low population in Class 1. The marital status of caregiver (OR = 0.067, 95% CI: 0.006, 0.700, P = 0.024), IA type (OR = 1.745, 95% CI: 1.198, 2.541, P = 0.004), children aged < 2 years (OR = 3.219, 95% CI: 1.364, 7.597, P = 0.008), social support (OR = 0.907, 95% CI: 0.865, 0.951, P < 0.001) and perception of uncertainty (OR = 1.054, 95% CI: 1.026, 1.083, P < 0.001) were associated with different caregiver reaction patterns. Conclusion: Nearly half of the caregivers of children with IA experience reaction of high burden and low benefit, but considerable proportion of caregivers could benefit from the caregiving rather than burden from. Married caregivers may have more negative reaction, especially when children < 2 years and diagnosed with intermediate or high type of IA. However, increasing caregivers’ social support and reducing perception of uncertainty may have the potential to modify their reaction pattern.